Spin-resolved photoemission study of epitaxially grown MoSe2 and WSe2 thin films. (12th September 2016) - Mo, Sung-Kwan; Hwang, Choongyu; Zhang, Yi; Fanciulli, Mauro; Muff, Stefan; Hugo Dil, J; Shen, Zhi-Xun; Hussain, Zahid
Abstract: Few-layer thick MoSe2 and WSe2 possess non-trivial spin textures with sizable spin splitting due to the inversion symmetry breaking embedded in the crystal structure and strong spin–orbit coupling. We report a spin-resolved photoemission study of MoSe2 and WSe2 thin film samples epitaxially grown on a bilayer graphene substrate. We only found spin polarization in the single- and trilayer samples—not in the bilayer sample—mostly along the out-of-plane direction of the sample surface. The measured spin polarization is found to be strongly dependent on the light polarization as well as the measurement geometry, which reveals intricate coupling between the spin and orbital degrees of freedom in this class of material.